MIFO fas 1 - Inventering av förorenade områden i Eslövs kommun och identifiering av osäkerheter - Ilioska,Anastasia (2025)
Industrial activities, mining and waste management have resulted in extensive contamination of soil, surface water and groundwater all over the world. Around the world, there are different methods used to classify contaminated sites into different risk classes. In Sweden, the method for the inventory of contaminated sites (MIFO) is used. Naturvårdsverket developed it in 1999. MIFO is divided into two phases. The work consists of two MIFO phase 1 studies. MIFO phase 1 was carried out on the properties Mörten 29 and Skruvmejseln 3 in Eslöv municipality. After reviewing different types of data, assessments were made. This resulted in a comprehensive risk assessment for each property. The collected data was assessed with the different MIFO-aspects in consideration. These are the hazard of the pollutants (F), pollution level (N), dispersion conditions, sensitivity (K) and protection value (S). The investigation resulted in Mörten 29 being given risk class 3 and Skruvmeyseln 3 being given risk class 2. Both properties have ongoing operations that fall under the category manufacturing industry without halogenated solvents according to Branschlistan förorenade områden (2025) from Naturvårdsverket. Despite that, it is the surrounding land use that has been a very decisive factor in Skruvmeyseln 3 being given a higher risk class than Mörten 29. In addition to risk classifying two properties, several uncertainties with the method have also been identified. This was made with two literature searches but also a review of the own data. Uncertainties that was identified are results based on assessments, that the assessor's expertise can vary, large scope for interpretation, incomplete completion of the MIFO documents, lack of data, discontinuous updating of various maps and risk of important data being omitted.
Keywords: MIFO; fas 1; förorenade områden; riskklass; arkivmaterial; osäkerhet; litteratursökning.